Question
upstudy study bank question image url

\( 1 \leftarrow \) For \( f(x)=\frac{x}{x-4} \) and \( g(x)=-\frac{9}{x} \), find the following composite functions and state the domain of each. \( \begin{array}{llll}\text { (a) } f \circ g & \text { (b) } g \circ f & \text { (c) } f \circ f & \text { (d) } g \circ g\end{array} \) (a) \( (f \circ g)(x)=\square \) (Simplify your answer. Use integers or fractions for any numbers in the expression.)

Ask by Sandoval Murphy. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

(a) \( (f \circ g)(x) = \frac{9}{9 + 4x} \) Domain: \( x \neq 0, x \neq -\frac{9}{4} \) (b) \( (g \circ f)(x) = -9 + \frac{36}{x} \) Domain: \( x \neq 4, x \neq 0 \) (c) \( (f \circ f)(x) = \frac{x}{-3x + 16} \) Domain: \( x \neq 4, x \neq \frac{16}{3} \) (d) \( (g \circ g)(x) = \frac{81}{x^2} \) Domain: \( x \neq 0 \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Mind Expander

To find the composite functions \( f \circ g \) and the others, we first start with their definitions and the functions provided: 1. **Calculating \( f \circ g \)**: \[ (f \circ g)(x) = f(g(x)) = f\left(-\frac{9}{x}\right) \] Now substituting \( g(x) \) into \( f(x) \): \[ f\left(-\frac{9}{x}\right) = \frac{-\frac{9}{x}}{-\frac{9}{x} - 4} = \frac{-\frac{9}{x}}{-\frac{9 + 4x}{x}} = \frac{-9}{-9 - 4x} = \frac{9}{9 + 4x} \] Therefore, \[ (f \circ g)(x) = \frac{9}{9 + 4x} \] 2. **Finding the domain of \( f \circ g \)**: - The function \( g(x) \) is defined for all \( x \neq 0 \). - The function \( f(x) \) is defined as long as \( x \neq 4 \). - Here \( g(x) = -\frac{9}{x} \) must not equal 4, i.e., \( g(x) \neq 4 \). - Thus, solving \( -\frac{9}{x} = 4 \) gives \( x = -\frac{9}{4} \). So the domain for \( f \circ g \) is \( x \in \mathbb{R}, x \neq 0, x \neq -\frac{9}{4} \). --- 3. **Calculating \( g \circ f \)**: \[ (g \circ f)(x) = g(f(x)) = g\left(\frac{x}{x-4}\right) \] Now substituting \( f(x) \) into \( g(x) \): \[ g\left(\frac{x}{x-4}\right) = -\frac{9}{\frac{x}{x-4}} = -\frac{9(x-4)}{x} = -\frac{9x - 36}{x} = -9 + \frac{36}{x} \] Therefore, \[ (g \circ f)(x) = -9 + \frac{36}{x} \] 4. **Finding the domain of \( g \circ f \)**: - The function \( f(x) \) is defined for \( x \neq 4 \). - The function \( g(x) \) is defined as long as \( g(x) \neq 0 \). In this case, \( g(f(x)) \) is defined when \( \frac{x}{x-4} \neq 0 \), which holds for all \( x \neq 0 \). - The restrictions are that \( x \neq 4 \) and \( x \neq 0 \). So the domain for \( g \circ f \) is \( x \in \mathbb{R}, x \neq 0, x \neq 4 \). --- 5. **Calculating \( f \circ f \)**: \[ (f \circ f)(x) = f(f(x)) = f\left(\frac{x}{x-4}\right) \] Now substituting into \( f(x) \): \[ f\left(\frac{x}{x-4}\right) = \frac{\frac{x}{x-4}}{\frac{x}{x-4} - 4} = \frac{\frac{x}{x-4}}{\frac{x - 4(x-4)}{x-4}} = \frac{\frac{x}{x-4}}{\frac{-3x + 16}{x-4}} = \frac{x}{-3x + 16} \] Therefore, \[ (f \circ f)(x) = \frac{x}{-3x + 16} \] 6. **Finding the domain of \( f \circ f \)**: - The initial restriction is \( x \neq 4 \). - We also check for when \( f(f(x)) \) is undefined (denominator equals zero): \( -3x + 16 \neq 0 \) implies \( x \neq \frac{16}{3} \). Thus, the domain for \( f \circ f \) is \(

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy